2011
DOI: 10.15193/zntj/2011/74/028-038
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fatty Acid Composition in Mare’s and Cow’s Milk Fat

Abstract: JAROSŁAWA RUTKOWSKA, AGATA ADAMSKA, MAŁGORZATA BIAŁEK  PORÓWNANIE SKŁADU KWASÓW TŁUSZCZOWYCH ZAWARTYCH W TŁUSZCZU MLEKA KLACZY I KRÓW S t r e s z c z e n i e Celem pracy była ocena składu kwasów tłuszczowych (KT) tłuszczu mlecznego klaczy i porównanie ze składem KT tłuszczu mleka krowiego, ze szczególnym uwzględnieniem KT istotnych w żywieniu człowieka. Materiał badawczy stanowiło 10 prób mleka klaczy i 10 prób mleka krowiego, pobieranych od zwierząt w okresie żywienia zimowego i letniego, z regionu mazowieck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 6 publications
(24 reference statements)
1
14
0
Order By: Relevance
“…Other authors' studies also support similar trends in fatty acid compositions in cow and mare milk fat (26).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Other authors' studies also support similar trends in fatty acid compositions in cow and mare milk fat (26).…”
Section: Discussionsupporting
confidence: 67%
“…Nutritional values of food depend on the proportion of n-6 to n-3 fatty acids, where the optimal proportion in milk fat is average 3-4:1. Fatty acid composition in milk fat is influenced by many factors, such as the animal's nutrition, breed, lactation, and age (22,26,30).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, even a minor detail such as the time of the day may have an impact on the content of some nutrients [108,109]. Additionally, the milk fat fatty acid profile is influenced by many factors, such as breed, period of lactation, nutrition, age and also the presence of environmental pollution [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…Milk composition is highly variable and differs even in the following days of lactation. Moreover, genetic, physiological, and nutritional factors, as well as environmental conditions, play a great role in making these differences [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…According to Malacarne et al (2002), human and cow milk have higher proportions of C16:0 than horse milk: 28.1%, 29.5%, and 23.8%, respectively. Rutkowska et al (2011) also reported lower levels of this acid in horse milk (winter feeding -23.12% and summer feeding -17.92%) than in cow milk (32.16 and 30.41%, respectively). Among MUFAs, both cow milk and horse milk contain oleic acid (C18:1n-9), in comparable proportions, i.e.…”
Section: Discussionmentioning
confidence: 84%